2012
DOI: 10.9721/kjfst.2012.44.1.094
|View full text |Cite
|
Sign up to set email alerts
|

The Skin Protecting Effects of Ethanolic Extracts of Eggplant Peels

Abstract: We investigated the in vitro antioxidant and antimelanogenesis effects of ethanol extracts from eggplant (Solanum melongena L.) peels. The total phenolics and chlorogenic acid in ethanol extracts were 2,465 mg/100 g and 2.08 mg/100 g, respectively. ABTS radical scavenging activity, ferric reducing/antioxidant power assay, and malondialdehyde (MDA) inhibitory effect of the extracts increased in a dose-dependent manner. In addition, the extracts generally showed strong UV absorption in the range of UV-B (290-320… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
1
3
0
1
Order By: Relevance
“…The leaf was the part of the plant with the highest inhibition (IC 50 689.5 µg/mL), while the root, stem, and fruit showed inhibition at concentrations above 2000 µg/mL ( Table 3 ). A study by Jo et al [ 83 ] reports an IC 50 of eggplant peel of approximately 1000 µg/mL, values with greater inhibitory activity of the radical concerning those found in this study in fruit (pulp and peel), comparable only to what was found in leaves. Moreover, in ten eggplant genotypes, Sharma et al [ 84 ] reported IC 50 values between 61.59 and 92.21 µg/mL.…”
Section: Resultssupporting
confidence: 52%
“…The leaf was the part of the plant with the highest inhibition (IC 50 689.5 µg/mL), while the root, stem, and fruit showed inhibition at concentrations above 2000 µg/mL ( Table 3 ). A study by Jo et al [ 83 ] reports an IC 50 of eggplant peel of approximately 1000 µg/mL, values with greater inhibitory activity of the radical concerning those found in this study in fruit (pulp and peel), comparable only to what was found in leaves. Moreover, in ten eggplant genotypes, Sharma et al [ 84 ] reported IC 50 values between 61.59 and 92.21 µg/mL.…”
Section: Resultssupporting
confidence: 52%
“…Such antioxidant activity has been shown to inhibit melanin production (24). To evaluate the influence of experimental sample, we analyzed the total polyphenolic content of experimental extracts.…”
Section: Resultsmentioning
confidence: 99%
“…The ultrasound-assisted extraction of anthocyanins was applied to several other fruits such as raspberries, mulberries, and grape seeds (Chen et al, 2007;Ghafoor et al, 2009). The importance of the eggplant peel extract derives from the fact that it is considered an important source of bioactive compounds (anthocyanins, phenolic compounds) and that these types of extracts can be used as natural antioxidants or as natural pigments for food products (Jo et al, 2012). In the current study, the eggplant peel extracts were obtained using the ultrasoundassisted extraction with three different solvents.…”
Section: Introductionmentioning
confidence: 99%